Responsible leadership and organisational citizenship behaviour for the environment: mediated by environmental corporate social responsibility - Sahar, Noor e; Zawawi, Dahlia; Jaharuddin, Nor Siah; Abbasi, Munir A. (Emerald Publishing, 2023)
Purpose: This study aims to use stewardship theory to investigate the effect of responsible leadership (RL) on organisational citizenship behaviour for the environment (OCBE) through the mediatory role of environmental corporate social responsibility (ECSR). Design/methodology/approach: Data was collected from a sample of 224 individuals employed in the manufacturing sector of Pakistan. The study used partial least squares structural equation modelling to estimate the relationships within the model. Findings: The findings indicate that RL positively impacts OCBE, and ECSR is a partial mediator that mediates the relationship between RL and OCBE. Practical implications: This research offers novel perspectives for organisational leaders, highlighting the significance of RL quality for instilling OCBE among the employees of manufacturing sectors. Organisational leaders must prioritise ECSR in their CSR initiatives. Originality/value: This study’s novelty lies in confirming the mediating role of ECSR to drive the positive impact of RL on OCBE through stewardship theory.